The power of music : pioneering discoveries in the new science of song - Mannes, Elena (Walker & Co., 2011)
This book is a pathbreaking exploration into how and why the human organism is moved by the undeniable effect of music. As Elena Mannes reveals we are at a breakthrough moment in music research, for only recently has science sought in earnest to understand and explain the power of music and its connection to the body, the brain, and the world of nature. From neurologist Gottfried Schlaug and X-ray astronomer Andrew Fabian, who studies the actual music of the spheres, to opera star Deborah Voigt and the deaf Scottish percussionist Evelyn Glennie, who "hears" through her feet, Mannes takes us to the crossroads of science and culture--Publisher description.